2014
DOI: 10.1016/j.jmii.2013.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of virulence genes to clinical manifestations and outcome in patients with Streptococcus dysgalactiae subspecies equisimilis bacteremia

Abstract: In invasive SDSE infections, most isolates carry putative virulence genes, such as scpA, ska, saga, and slo. Clinical SDSE isolates in Taiwan remain susceptible to penicillin cefotaxime, and levofloxacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 28 publications
1
25
1
1
Order By: Relevance
“…The three strains proved negative for a series of streptococcal superantigen virulence genes (speA, speC, speG, speH, speI, speJ, speK, speL, speM, ssa, smez); however, they were positive for nonsuperantigenic virulence genes (scpA, ska, slo, and sagA), as previously documented [5]. Furthermore, the strains were investigated by multilocus sequence typing (MLST) to determine their genotypic characteristics.…”
Section: Case Reportsupporting
confidence: 53%
See 3 more Smart Citations
“…The three strains proved negative for a series of streptococcal superantigen virulence genes (speA, speC, speG, speH, speI, speJ, speK, speL, speM, ssa, smez); however, they were positive for nonsuperantigenic virulence genes (scpA, ska, slo, and sagA), as previously documented [5]. Furthermore, the strains were investigated by multilocus sequence typing (MLST) to determine their genotypic characteristics.…”
Section: Case Reportsupporting
confidence: 53%
“…Characterization of isolate virulence was conducted by multiplex PCR according to the primers and method previously described [5]. The three strains proved negative for a series of streptococcal superantigen virulence genes (speA, speC, speG, speH, speI, speJ, speK, speL, speM, ssa, smez); however, they were positive for nonsuperantigenic virulence genes (scpA, ska, slo, and sagA), as previously documented [5].…”
Section: Case Reportmentioning
confidence: 65%
See 2 more Smart Citations
“…equisimilis (SDSE) has increasingly been recognized as the aetiological agent of several human invasive infections worldwide (Bruun et al, 2013;Sunaoshi et al, 2010;Takahashi et al, 2010Takahashi et al, , 2011Tsai et al, 2014). SDSE isolates are frequently classified as Lancefield group C or G. Comparative genomic analyses revealed that several commonly found group A streptococci virulence factors have also been detected in SDSE isolates, including C5a peptidase, M protein, glyceraldehyde 3-phosphate dehydrogenase, hyaluronidase, streptokinase, streptolysin O and streptolysin S, amongst others (Reissmann et al, 2012;Sunaoshi et al, 2010;Suzuki et al, 2011;Watanabe et al, 2013).…”
Section: Introductionmentioning
confidence: 99%